Crescimento inicial e morfologia foliar em plantas de Enterolobium contortisiliquum (Vell.) Morong. E Erythrina velutina Mart. ex Benth, sob estresse hídrico - Dantas, Sebastião Gilton (2014)
The Caatinga is the predominant vegetation type in semi-arid region of Brazil, where many inhabitants depend on hunting and gathering for survival, obtaining resources for: food and feed, folk medicine, timber production, etc. It‟s the dry ecosystem with highest population density in the world. The early stages of development are the most critical during the life cycle of a flowering plant and they‟re primordial to its establishment in environments exposed to water stress. Information about adjustments to the growth of the species, correlated with their studies of distribution in Seridó oriental potiguar, are an important ecological and economic standpoint, because they provide subsidies for the development of cultivation techniques, to programs of sustainable use and recovery of degraded areas. This thesis aimed to study the initial growth and foliar morphology in plants like Enterolobium contortisiliquum (Vell.) Morong. (tamboril) and Erythrina velutina Mart. ex Benth (mulungu), species of occurrence in the Caatinga, under water stress. After sowing and emergency, the seedlings were exposed to three water regimes: 450 (control), 225 (moderate stress) and 112.5 (severe stress) mm of water slide for 40 days. Seeding occurred in bags of 5 kg and after the establishment of seedlings thinning was carried out leaving a plantlet per bag. At the beginning the waterings occurred daily with distilled water, passing to be on alternate days after thinning. Twenty and forty days after the thinning seedlings collections were held to be done analysis of growth and biomass partition. When compared to the control group, the treatments with water stress showed reduction in the growth of the aerial part, growth of the greater root, number of leaves and leaflets, dry leaf area and total phytomass in both species, but in general, this effect was most marked for E. velutina. Regarding the partition of biomass, there were few changes throughout the experiment. Morphological changes in the leaves as a function of stress were not significant, however, there was a trend, in both species, to produce narrower leaves, that facilitate heat loss to the environment. It has not been possible to establish a positive relationship between inhibition of growth and distribution of species, whereas E. velutina is a species of most common occurrence in Seridó oriental potiguar. In this way, other aspects should be taken into account when studying the adaptation of species the dry environments, such as salinity, presence of heavy metals, wind speed, etc